Assises contre le racisme - Langenaken, Dominique (Bruxelles: MRAX, 1982)
"Réalisé par Dominique Langenaken,... et al. Fonds VCIMBevat bijdragen van Mateo Alaluf, Véronique De Rudder, Alain De Wasseige, Monique Dujardin, Angel Enciso, Thérèse Gastaut, Claude Geets, Albert Jacquard, Marcel Liebman, Albert Martens, Frank Moulaert, Me Pau-Langevin, Paulette Van Gansen"